Identity, crimes, and law enforcement in the Metaverse - Hua Xuan Qin; Yuyang Wang; Pan Hui (Humanities & Social Sciences Communications)
Abstract The recent Metaverse technology boom in major areas of the public’s life makes the safety of users a pressing concern. Though the nature of the Metaverse as a geographically unbounded space blending the physical and the virtual presents new challenges for law enforcement and governance. To tackle these, this paper supports the establishment of a unified international legal framework. Specifically, from a law enforcer’s perspective, it provides the first comprehensive discussion in the past five years on legal concerns related to identity, various types of potential crimes, and challenges to unified law enforcement in the Metaverse based on prior incidents.